The efficient interleaving of digital-video-broadcasting-satellite 2nd generations system - Mohammed Jabbar Mohammed Ameen; Hussam Jawad Kadhim (Universitas Ahmad Dahlan, 2020)
The DVB-S2 system is designed as a toolbox to permit the execution of the satellite programs. Interleaver is an essential part of the DVB-S2 system. The current general block interleaver in DVB-S2 is not best, which leads to high BER and maybe not satisfy the requirements of the system. The purpose of this paper is to study the several interleaver types and comparative analyses are done between them to find which of these give better performance. Simulations results obtained prove that the 2D interleavers minimize BER more than other interleavers of DVB-S2. Further, the performance of 2D interleaver is better on a system that required a low SNR.